Analisis Dampak Program Susu Gratis terhadap Peningkatan Human Capital Index di Indonesia: Studi Literatur dengan Perbandingan Implementasi di India - Adestria, Elga; Agung Risdhianto; Hikmat Zakky Almubaroq (CV. AFDIFAL MAJU BERKAH, 2025)
Improving the quality of human resources (HR) is a critical element of Indonesia's long-term development agenda. The Human Capital Index (HCI) is used as a key measure of a nation's HR capacity, encompassing health, education, and workforce skills. A higher HCI signifies a stronger potential for economic growth and social development. One of the essential factors in boosting HCI is children's nutrition, as it directly influences their physical and cognitive development. Programs like free school milk distribution, which have been implemented in various countries such as Indonesia and India, aim to enhance children's nutritional status, thereby improving their learning outcomes, long-term health, and future productivity. This study examines the impact of Indonesia’s free milk program on improving HCI by conducting a comprehensive literature review. It also compares the implementation and effectiveness of similar programs in India to identify best practices. The study highlights several challenges faced by Indonesia, including limited infrastructure, funding constraints, and insufficient public awareness, all of which hinder the program’s success. In contrast, India’s successful milk distribution programs, supported by strong government policies, public-private partnerships, and extensive community engagement, provide valuable lessons for Indonesia. The research suggests that by adopting India’s strategies, such as improving distribution networks, increasing funding, and enhancing public education on nutrition, Indonesia could significantly strengthen its free milk program. The findings offer policymakers practical recommendations to improve child nutrition and, consequently, Indonesia’s HCI, leading to stronger economic growth and social progress in the future.